WHY DO THE ELDERLY KEEP WORKING? - Sri Rekno Galuh Sitoresmi; Istiqomah Istiqomah; Sukiman Sukiman (TRIKONOMIKA, 2020)
The elderly population are considered unproductive. However, in Kalisari village, many older people continue to work. This study aims to determine the effect of age, education level, number of dependents and other income on the elderly's decision to work. Primary data were collected using interview based on questionnaires. The population consists of 144 people aged 60+ comprising of 84 people who are unemployed and 60 unemployed. In this study, the determination of the minimum sample size was carried out with the Slovin formula to choose 60 respondents consisting of 30 employed and 30 unemployed. Data analysis using binary logistic regression shows that age and education level do not have a significant effect on the elderly population's decision to work, while other income has a significant negative effect and the number of family dependents has a significant positive effect on the elderly's decision to work.